PENANGANAN LONGSORAN RUAS JALAN PRUPUK – BTS. BANYUMAS (CIREGOL, KEC. TONJONG, KAB. BREBES) PADA KM. PKL 115+550 s/d KM. PKL 115+650 - Maria Handayani S.; Yosef Aryanto; Siti Hardiyati; Bambang Pardoyo (Jurnal Karya Teknik Sipil, 2013)
This Final Project contained about the stability of the soil and it countermeasures on roads Prupuk - Bts. Banyumas, Ciregol, sub-district. Tonjong, district of Brebes. The Landscape around Ciregol is topography ridge sloping area that is very close to the river valley times pedes and prone to landslide. This road is a national road that connects the Tegal city - Purwokerto city and including the road class II which is  built to connect the regions, thus supporting economic growth in the region and surrounding Ciregol. This road crosses the hills that contain layers of silt, sand and clay stone. Slope landslide occurred on roads Prupuk - Bts. Banyumas KM. PKL. 115+650  and between range time of February to March 2012 has occurred 4 times landslides. This final project analyzes value of the slope safety factor that included a condition when occured of the movement of soil slopes which is caused by instability on slopes due to degradation of soil layers / rocks, manual calculation of slope stability using Fellinius method and Plaxis computer program . Location of countermeasures is taken along 100 m  from KM. PKL 115 +550 to KM. PKL 115 +650. From the analysis of data and computation known that the slip field of slope occurs at a depth of -28.5 m from the road surface. To deal with it,we try to used the alternative form to handling of landslides with reinforcement bored pile, each is 90 m and 25.6 m to the direction of for the transverse direction are applied to the cut slip field along the ridge of slope and combined with  reinforcement soil retaining walls, geotextile or gabion each tried installed at the same location at the foot of the slopes. Geotechnical analysis using Plaxis software. Model of plastic elastic  and collapse criterion  of Mohr-Coulomb chosen as the soil model . The analysis showed that reinforcement landslide with bored pile with diameter of 1.5 m is placed at the top, middle and bottom of the slope to a depth of 37 m, respectively, 37 m and 30 m in combination with the soil retaining wall at the foot of the slopes as high as 15 m with a thickness of 2-4 m is handling that has increased the value of the safety factor, where the factor of safety of the existing condition of the original which is from 1,053 become 1,536, but if considered from the results of Incremental Shear strains apparently it still has  little potential for landslides at the top of the slope, so  it added with the use of geotextile reinforcement on the upper slopes as high as 5 meters to overcome it. Safety factor with the additional reinforcement is increased to 1.973.